Effect of Different Concentration of Liquid Organic Fertilizer and Varieties on The Growth and Yield of Red Chili (Capsicum annuum L.) in Sandy Soil - Andre Setiyawan; Sri Devi Octavia (BPFP Universitas Bengkulu, 2025)
Sandy soils, characterized by high sand content (often exceeding 70-90%), exhibit low nutrient retention, poor water holding capacity, and reduced cation exchange due to their coarse texture and low organic matter. These properties pose significant challenges for red chili (Capsicum annuum L.) cultivation, often resulting in suboptimal growth and yield without amendments. This study aimed to evaluate the effects of varying concentrations of liquid organic fertilizer derived from vinasse and different red chili varieties on the growth and yield of red chili plants in such challenging soil conditions. The experiment was conducted in a greenhouse at the Faculty of Agriculture, Sarjanawiya Tamansiswa University, Yogyakarta. A 3 × 2 factorial design arranged in a Completely Randomized Design (CRD) with four replications was employed. The first factor consisted of liquid organic fertilizer concentrations at 5%, 6%, and 7%, while the second factor included two red chili varieties: F1 Gada and Prabu. Growth parameters measured were plant height, number of leaves, stem diameter, and number of branches. Yield components included fresh and dry plant weight, number of fruits, and fresh fruit weight. The results indicated no significant interaction between fertilizer concentration and chili variety on growth and yield parameters. However, the F1 Gada variety exhibited significantly greater fresh plant weight and number of fruits compared to Prabu. These findings suggest that selecting appropriate chili varieties, such as F1 Gada, combined with optimal liquid organic fertilizer concentration, can improve red chili production in sandy soils. This information is valuable for farmers and agricultural practitioners aiming to enhancecultivation efficiency and yield within sustainable farming systems. Full text pdf